Highly Commended Award Winner - Emerald Literati Network Awards for Excellence 2011 - Zopiatis, Anastasios (My University, 2026)
Highly Commended Award Winner - Emerald Literati Network Awards for Excellence 2011 for the paper: Zopiatis, A. and Constanti, P. (2010). Leadership styles and burnout: Is there an association? International Journal of Contemporary Hospitality Management, 22 (3), 300-320.
Keywords: Arts and entertainment